Professores? Sim! Os saberes docentes e os professores da Educação Profissional - Cardoso, Aliana Anghinoni (2012)
This dissertation reports the results of an investigation which, focused on the research field concerning teacher knowledge, aimed at identifying which knowledge the teachers working on Professional Education mobilize, acquire and build along their careers as teachers. Considering that most teachers of technical subjects in Professional Education start their careers without having any previous formal preparation for the teaching practice. Nine subjects were interviewed with the purpose of understanding how they have become teachers, which difficulties they faced, what they learned and how, what knowledge they have and, mainly, what they think about the process which built the teachers they are today. Among the main results reached in the context of this research, we highlight the fact that the teachers interviewed understand that there were many factors which interfered in their teaching. However, they affirm that with the time and the practice they had they learned and are still learning to be teachers. They identify that the Professional Education is a specific type of education and to teach in such context it is necessary to have a considerable knowledge which, when interrelated, enable the teacher to reach his/her main purpose which is to teach a profession. Among the knowledge pointed out in this investigation the knowledge concerning teaching; concerning the way of being and acting; concerning the purposes of educational action and the professional work are the ones we highlight.